Combined and mediating effects of remnant cholesterol and renal function on hypertension risk in Chinese middle-aged and elderly people - Zhao, Mengjie; Xiao, Mengli; Zhang, Huie; Tan, Qin; Ji, Jinjin; Cheng, Yurong; Lu, Fang (Frontiers in Endocrinology, 2025)
BackgroundEmerging evidence indicates a potential correlation between remnant cholesterol (RC) and the development of vascular damage and hypertension. Nevertheless, the precise relationship between RC and hypertension in relation to renal function remains uncertain. The objective of this investigation was to employ a cohort design to evaluate the intricate correlation between RC and renal function in relation to hypertension.MethodsThe present investigation utilized data from the China Health and Retirement Longitudinal Study (CHARLS), encompassing a total of 5,109 participants, for comprehensive data analysis and examination. Cox regression analysis was employed to examine the interplay among RC, renal function, and hypertension within the context of this research study. This study utilized restricted cubic spline (RCS) analysis to elucidate the interaction between RC, renal function, and hypertension, specifically examining the mediating role of renal function in the RC-hypertension nexus. Furthermore, we employed mediation analysis to investigate the potential mediating role of renal function in the association between RC and hypertension.ResultsAfter a 9-year follow-up period, the incidence of hypertension in the population under investigation was observed to be 19.01%. The Kaplan-Meier curves demonstrated a notable and statistically significant elevation in the prevalence of hypertension within the subgroup characterized by higher RC and impaired renal function (P <0.001). However, in Cox regression analyses, the risk of developing hypertension was significantly higher (P <0.05) in those with high RC and high estimated glomerular filtration rate (eGFR), and those with high RC and low eGFR, compared with those with low RC and high eGFR, after adjusting for confounders. The analysis of RCS demonstrated a significant positive linear correlation between baseline RC and the prevalence of hypertension. Additionally, there was a notable negative linear correlation observed between eGFR levels and the prevalence of hypertension. RC and eGFR did not interact with any of the subgroup variables. eGFR lowering mediated 6% of the associations between RC and hypertension.ConclusionThe findings of this study unveiled a substantial correlation between elevated RC, diminished eGFR levels, and the risk of developing hypertension. In addition, renal function may mediate the correlation between RC and hypertension risk.